The Algebraic Classification of Nilpotent Bicommutative Algebras - Kobiljon Abdurasulov; Ivan Kaygorodov; Abror Khudoyberdiyev (Mathematics, 2023)
This paper is devoted to the complete algebraic classification of complex five-dimensional nilpotent bicommutative algebras.